From science to sustainable systems: Evidence based-decision making for adolescent fertility in Zambia - Margarate N. Munakampe; Marte E.S.H. Haaland; Joseph M. Zulu; Charles Michelo (Elsevier, 2021)
Background: Adolescent fertility is a global health and sustainable development indicator, and requires robust information systems for priority setting and decision-making to control. Evidence-based decision making for health stresses the use of scientific objective data and methodologies, which typically sieve out the more contextually understood social and economic factors that impact health.Main Text: The rising adolescent fertility rates in Zambia warrant the use of robust information systems for planning and resource allocation. In addition to the shortage of information on adolescent health in general, the existing information systems are limited. Sustainable information systems require an investment in data collection that transcends the existing and heavily relied on quantitative evidence base on adolescent sexual and reproductive health, arguing for the need to include data generated through qualitative and participatory methodologies, generating a more holistic understanding of health phenomena.Conclusion: There is a need to collect data on adolescent fertility using alternative methods to make decisions that work for adolescents.